The Effectiveness of Using Mathematical Power Strategy in Developing Achievement of the Basic Seventh Grade Students in Jordan - Alsmadi , Mohareb (Dirasat: Educational Sciences, 2020)
This study aims at investigating the effectiveness of using mathematical power strategy in developing Basic Seventh Grade female students` achievement in Jordan. The Quasi-experimental design has been used, and achievement test has been conducted for the chosen unit in the light of Bloom`s first three taxonomies (knowledge, comprehension, application). A (60) Basic Seventh Grade female students have been selected as a purposive sample from the directorate of education in Ajloun government. Students have been distributed randomly on two groups, one has been taught by using mathematical power strategy as an experimental group, while the other has been taught by using the traditional way as a control group. The achievement test has been conducted as pre-post test on both groups, and the results indicated that there was no statistically significant difference at (α =0.05) between the two arithmetic means for the scores of students' in the achievement test at the level of recall, attributed to teaching method, but results of the study demonstrated that there were statistically significant difference between the two arithmetic means at (α = 0.05) for the scores of students in the achievement test at the level of (comprehension, application, overall score) attributed to the teaching method in favor of mathematical power strategy. The study recommended that the curriculum developers in the Ministry of Education can benefit from the Mathematical power as a method of teaching in addition to train teachers on using educational programs in it.